2016
DOI: 10.1515/sab-2016-0002
|View full text |Cite
|
Sign up to set email alerts
|

German Shepherd Dog Milk Composition and Its Changes During Lactation

Abstract: Milk composition of nine lactating German Shepherd nursing females was studied. The experiment took place at the breeding facility of Police of the Czech Republic (breeding centre for service dogs in Domažlice) in days 2−30 of the females’ lactation. Females were given a commercial granulated feeding mixture (starter category). Canine milk samples were analyzed using an infra-red instrument MilkoScan FT 120. Calculated mean values for colostrum (day 2 postpartum) and normal milk (days 4−29 postpartum) were: 23… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Our results are in contrast with those reported by Lönnerdal et al [ 28 ] who found in beagles lower protein contents and a significant increase in milk protein percentage during lactation (from 4.30 to 5.31% at 10 and 30 days of lactation, respectively). In German shepherd milk, Dokoupilová et al [ 29 ] reported a protein concentration varying from 7.08 to 7.51% from the 7th to 30th day of lactation. Similarly, to our results, Oftedal [ 30 ] reported a mean protein and fat concentration equal to 7.53 and 9.47%, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results are in contrast with those reported by Lönnerdal et al [ 28 ] who found in beagles lower protein contents and a significant increase in milk protein percentage during lactation (from 4.30 to 5.31% at 10 and 30 days of lactation, respectively). In German shepherd milk, Dokoupilová et al [ 29 ] reported a protein concentration varying from 7.08 to 7.51% from the 7th to 30th day of lactation. Similarly, to our results, Oftedal [ 30 ] reported a mean protein and fat concentration equal to 7.53 and 9.47%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, to our results, Oftedal [ 30 ] reported a mean protein and fat concentration equal to 7.53 and 9.47%, respectively. Several authors have reported a non-significant increase in fat content from day 10 to day 25 in German shepherds [ 29 , 31 ] and beagles [ 32 ]. These authors have suggested that the variations between studies may represent the actual differences between dog breeds and other factors, such as litter size and the characteristics (composition, energy intake micro- and micro-nutrients availability) of the diets administered to the bitches could probably also affect these results.…”
Section: Discussionmentioning
confidence: 99%
“…Little is known about the components of canine milk, specifically colostrum, and the knowledge related to its microbial and metabolic profiles is particularly underwhelming [ 13 ]. Following whelping, a puppy’s gut is seeded with microbes from various sources, one of which is the dam’s milk [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Canine species. (From Oftedal, 1984 , n = 5 bitches; Adkins et al, 2001 , n = 10; Macias Rostrami et al, 2014 , n = 7; Dokoupilova et al, 2016 , n = 9.) Green: lactose (g/l); black: dry matter (g/100 g); red: energy (kcal/cl); orange: lipids (g/100 g); blue: proteins (g/100 g).…”
Section: Introductionmentioning
confidence: 99%